WOMEN EDUCATION AND SOCIAL CHANGE IN ONDO, SOUTHWESTERN NIGERIA, 1875-2008 (2013)
Patriarchal system dominated traditional Ondo society as reflected in the preference for the education of boys. Despite the influence of modernity which leveraged the women with equal opportunity of education with men, existing literature on Ondo have not adequately addressed the issue of women education in the town. This study, therefore, examines the historical dynamics of women education and its impact on the society at the micro and macro levels between 1875 and 2008. George Peter Murdock and Ann Oakley's Sex and Gender analysis, complemented with Anthony Gidden's Theory of Social Change was adopted as the theoretical framework for this study. Primary data used for this study include archival materials (Intelligence Reports and Ondo Provincial Files at the National Archives, Ibadan), school records and oral interviews. The purposive and snowball interview approaches were adopted. Informants include professionals, education officers, traditional title holders, school girls and parents. Secondary data consist of books and other print materials, including theses and dissertations. Photographs and almanacs related to women education in Ondo were also utilized. Data were subjected to historical analysis to reflect changing trends. From inception of Western education in 1875 to 1906 when Ondo formally came under British colonial rule, girls' enrollment in primary schools was less than 20%. From 1906 to 1953, secondary education for girls was non-existent, though boys had been enjoying this since 1919. The implication is that women were excluded from all levels of colonial administration because of the apparent educational disparity. From 1954 to 2008, there had been a tremendous change in women education, especially with government policy on free and compulsory Universal Primary Education in 1955 and the founding of three girls' colleges in 1954, 1955 and 1985 respectively. Expanded female education led to women's increasing participation in politics and professions formerly considered reserved for men. Over the years, women came to dominate nursing and teaching but fewer in medicine, engineering and other science-based professions. Before independence, female percentage in nursing was about 35% and medicine less than 3%. By 2008, it had risen to about 80% and 40% respectively. In teaching, the percentage in 1960 was about 30% in Primary schools and 13% in Secondary schools. By 2008, it had increased to about 90% and 65% respectively. Despite women's educational advancement, Ondo society remains essentially male-dominated and the society continues to perceive women in relation to their domestic roles as indicated in interviews conducted. This reinforces the argument that rather than being the inventors of gender binary, colonialism only exacerbated an already contrary condition. Expanded female education and consequent participation in the labour market has led to financial emancipation and improved status for women, but the full social identity of the woman is hampered by the patriarchal nature of the Ondo Society. There is therefore a need for cultural re-orientation in the reality of persisting male dominance in Ondo.